Bread, Politics and Political Economy in the Reign of Louis XV Second Edition (Edition 2) - Reinert, Sophus A. (Anthem Press, 2015)
A new edition of Kaplan's landmark study on eighteenth-century French political economy, reissued with a new Foreword by Sophus A. Reinert. Based on research in all the Parisian depots and more than fifty departmental archives and specialized and municipal libraries, Kaplan's classic work constitutes a major contribution to the study of the subsistence problem before the French Revolution and the political economy of deregulatory reform. Anthem Press is proud to reissued this pathbreaking work together with a significant new historiographic companion volume by the author, "The Stakes of Regulation: Perspectives on 'Bread, Politics and Political Economy' Forty Years Later."